The Influence of Mathematical Anxiety, Self Efficacy, and Learning Motivation on Student’s Problem Solving Ability in Vocational High School: Case Study in SMK Negeri 1 Maluku Tengah - Kappuw, Tresye Matelda (International Journal of Business, Law, and Education, 2025)
This study examines the influence of mathematical anxiety, self-efficacy, and learning motivation on students’ problem-solving ability in vocational education, with a case study at SMK Negeri 1 Maluku Tengah. Using a quantitative correlational design, data were collected from 126 Grade XI students selected through proportionate stratified random sampling. Mathematical anxiety, self-efficacy, and learning motivation were measured using validated questionnaires, while problem-solving ability was assessed through a test based on Polya’s four-step problem-solving framework. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that mathematical anxiety has a significant negative effect on problem-solving ability (β = -0.312, p < 0.001), while self-efficacy (β = 0.428, p < 0.001) and learning motivation (β = 0.316, p < 0.001) have significant positive effects. The model explains 63.2% of the variance in problem-solving ability. These findings highlight the importance of addressing affective factors such as anxiety, as well as strengthening self-efficacy and motivation, to enhance students’ problem-solving performance in vocational high schools.